1993
DOI: 10.1128/jvi.67.7.4391-4394.1993
|View full text |Cite
|
Sign up to set email alerts
|

An African swine fever virus gene with similarity to the proto-oncogene bcl-2 and the Epstein-Barr virus gene BHRF1

Abstract: An open reading frame, LMW5-HL, in the African swine fever virus genome displays a high degree of similarity to the proto-oncogene bcl-2 and, to a lesser degree, the Epstein-Barr virus gene BHRFI. A highly conserved central region is found in all three proteins. LMW5-HL encodes a protein of 18 kDa that is present in infected porcine macrophages at both early and late times postinfection. The similarity ofLMWS-HL to bcl-2 and BHRFI suggests a role for it in cell maintenance during productive or persistent viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(57 citation statements)
references
References 40 publications
0
56
0
1
Order By: Relevance
“…BCI-XL, a Bcl-2-like protein from chicken, can also suppress apoptosis of mammalian cells (Boise et al, 1993), and a number of viruses also express Bcl-2-like cell death suppressors [e.g. adenovirus E1B 19k (Rao et al, 1992), Epstein-Barr virus BHRF1 (Henderson et al, 1993) and African swine fever virus LMW5-HL (Neilan et al, 1993)]. In addition, some cell death suppressors have been identified that appear to be unrelated to Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…BCI-XL, a Bcl-2-like protein from chicken, can also suppress apoptosis of mammalian cells (Boise et al, 1993), and a number of viruses also express Bcl-2-like cell death suppressors [e.g. adenovirus E1B 19k (Rao et al, 1992), Epstein-Barr virus BHRF1 (Henderson et al, 1993) and African swine fever virus LMW5-HL (Neilan et al, 1993)]. In addition, some cell death suppressors have been identified that appear to be unrelated to Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that viruses like Epstein Barr virus (EBV) and African swine fever virus (ASFV) encode genes homologous to bcl-2 and are implicated in PCD. BRFHl of EBV encodes for a protein that is abundantly expressed early in the lytic replication cycle and is also transiently expressed in some latently infected lymphoid cells (Marchini et al 1991, Neilan et al 1993. It has been proposed that BHRFl may subtitute for bcl-2 in cells undergoing productive infection, when virus-induced shut-down of host cellular genes may result in bcl-2 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…7). The viral Bcl2 homolog (vBcl2) A179L/5HL is a conserved, essential gene encoding a 19-kDa protein named p21 (Neilan et al, 1993;Revilla et al, 1997). A179L protects cells from apoptosis, even when expressed in heterologous systems such as VACV or baculovirus (Brun et al, , 1998.…”
Section: Apoptosis Inhibitor Asfv Genesmentioning
confidence: 99%